Likang Telu: Cultural Basis for Muslim-Catholic Relations in Manggarai - Hironimus Bandur; Adison Adrianus Sihombing (Al-Albab, 2022)
This article explores the power of culture as an effort to promote a harmonious, tolerant and peaceful life between Muslims and Catholics. Likang telu is a cultural concept of the people of West Flores which is the basis for Muslims and Catholics to live in harmony, tolerance and peace. This study was conducted in Manggarai, West Flores, East Nusa Tenggara Province. The work aims to explore four elements including, 1) the differences in Muslim-Catholic relations after and before the reform era; 2) the extent to which the likang telu concept affects Muslim-Catholic relations in Manggarai; 3) the reasons for the likang telu concept being ignored by the Manggarai people and 4) the implications of the fading likang telu concept in Muslim-Catholic relations in Manggarai. The sugests that before the reform era, the Muslim and Catholic communities could live side by side in harmony and peace, while after the reform, the situation changed and conflicts were inevitable. It is apparently due to fading local wisdom, namely the likang telu concept of the Manggarai people which has 3 pillars: ase-kae (brother and sister), hae beo (fellow residents), and anak wina-anak rona (husband-giver and wife-giver). The trigger factors are the emergence of religious organizations both in the Catholic Church and in Islam; preferences of people’s knowledge sources that rely on the social media; and the unresolved trauma of the Muslim-Catholic relations in the past. The disregard for local wisdom has negative implications for Muslim-Catholic relations in Manggarai. This study recommends that all elements of the Manggarai community should revive and socialize likang telu as a local cultural treasure that had been proven in the past to be able to build a bridge of interfaith relations among different Manggarai communities.